Epidemiology, Clinical Features and Treatment of Neurosarcoidosis in Northern Spain - Alba Herrero-Morant; Raúl Fernández-Ramón; Diana Prieto-Peña; José Luis Martín-Varillas; Santos Castañeda; Ricardo Blanco (Biomedicines, 2025)
Objectives: Neurosarcoidosis (NS) is a severe and infrequent complication of sarcoidosis. Available data on NS are variable. We aimed to characterize NS epidemiology, clinical and therapeutic characteristics in a well-defined cohort of NS patients. Methods: Observational population-based cohort study of 342 patients diagnosed with sarcoidosis in Northern Spain, between 1999 and 2019. Among them, those patients who fulfilled the Consortium Consensus Group diagnosis criteria for NS were included. The annual incidence between 1999 and 2019 was estimated by gender, age, and year of diagnosis. Additionally, a literature review was performed. Therapeutic efficacy was evaluated using the neurological-related extra-pulmonary physician organ severity tool (ePOST). Results: NS was diagnosed in 29 out of 342 patients with sarcoidosis (8.5%; 18 women/11 men) with a mean age of 42.3 ± 15.1 years. Most NS patients have associated systemic sarcoidosis (93.4%) mainly consisting of lung (n = 22; 75.9%), articular (n = 15; 51.7%) and/or ocular (n = 12; 40%) involvement. The annual incidence of NS during the study period was 1.1 per 1,000,000 people. There is a linear relationship with a weak decrease in age at diagnosis over time. NS was subdivided into chronic headache (n = 11; 36.7%), cranial neuropathy (n = 7; 24.1%), myelitis (n = 4; 13.8%), peripheral neuropathy (n = 3; 10.3%), cranial neuropathy with chronic headache (n = 3; 10.3%) and aseptic meningitis (n = 2; 6.9%). Twenty-five patients (86.2%) received oral glucocorticoids (mean ± SD maximum prednisone dose 49.6 ± 19.4 mg/day). In addition, conventional immunosuppressive drugs were administered to 17 (58.6%) patients and biological therapy to 12 (41.4%) patients. After 12 months of initiating biological therapy, 14 out of 17 patients (82.4%) achieved complete remission, defined as an ePOST score of 0. Severe allergic reaction was observed in only one patient who had received treatment with both Infliximab and Adalimumab. Conclusions: The epidemiological, clinical and treatment characteristics of NS in Northern Spain are similar to that of other countries.